Microstructure and Properties of Al2O3-Y3Al5O12 Reactive Sintered Ceramic Composites with Multilayer Compositional Gradient: an Initial Investigation - Vinícius Z. Bôsco de Souza; Bruno Medeiros da Silva; Bruno Xavier de Freitas; José Eduardo Vasconcelos Amarante; Paula Cipriano da Silva Vidal; Ésoly Madeleine Bento dos Santos; Claudinei dos Santos (Materials Research, 2023)
In this work, mixtures of ceramic powders containing Al2O3 with different amounts of Y2O3 (1%, 3%, 5% and 10wt.%) along their cross-section were fabricated to obtain multilayer composites based on Al2O3 with different levels of Y3Al5O12 (YAG) as reinforcement. Monolithic cylindrical multilayer Al2O3 blocks were compacted and subsequentially, sintered at 1610°C for 4h. Phase stability, microstructural aspects, and physical and mechanical properties of the specimens were acquired by relative density, X-ray diffraction, scanning electron microscopy, Vickers hardness, fracture toughness, Young’s modulus and biaxial flexural strength measurements. The results indicated that monolithic alumina specimens exhibited relative density of 98%, with average hardness of 1203 ±83 HV, fracture toughness of 2.1 ±0.8 MPa.m1/2 and flexural strength of 187 ±64 MPa. Progressive incorporation of Y2O3 into the chemical composition of the specimens led to formation of the YAG phase by solid state reaction during sintering, which reduced hardness and increased densification, fracture toughness and flexural strength, with average values of HV=1023 ±28 HV, KIC=3.5 ±0.3 MPa.m1/2, σf=273 ±58 MPa and 14% Y3Al5O12 for the specimens with 10wt.% Y2O3. This improvement is probably associated with toughness mechanisms, such as crack deflection and residual thermal stresses between the phases present in the composites.